The Law Enforcement Of The Employees Social Security System In Indonesia: A Game Theory Perspective - Amsyari, Randy; Dwi Kesumah, Fajrin Satria (FEB - Universitas Lampung, 2019)
Insurance for the workers means a guarantee of safety for their works on the workplaces. It is necessarily crucial as workers need such a policy that can protect them from the loss. Indonesian government declare a policy that enact the act about National Social Security System (SJSN). The companies are the subject of this regulation, despite the fact at the initial implementation of this law enforcement brought to the pros and cons. Hence, the regulation also regulates for those who betray the policy will have to pay some certain amount of fine which in turn can harden them. The companies on the other side have a choice either to register or not their workers to SJSN as they still consider the premium they have to pay. This study aims to analyze the payoffs for both government and companies to be better off from the law enforcement. Game theory perspective is applied for the methodology of the study, particularly Subgame Perfection Nash Equilibrium (SPNE) and Bayesian Nash Equilibrium (BNE). The results present that in condition of an effective law enforcement at p, the firms will be beneficial from the SJSN policy by registering their workers and pay the premium, because if they do not pay the premium they have to pay additional amount of fine. On the other hand, if the policy is not effective with 1-p, the firms will have an advantage by not registering their employees to the SJSN as the law enforcement is not effective. Also, the government does not necessarily conduct an investigation as the cost is higher than the return that they will get.